Gamification in Lifestyle - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (International Journal of Human Computing Studies, 2023)
Gamification is a transformation of something into a game. It is applying game-like elements into everyday activities such as exercise to increase engagement and motivation through rewards. Applying game principles to everyday, mundane tasks can make life more exciting. Gamification uses the same motivational psychological principles that have always been around: self-affirmation, competition, peer support, and gratification through rewards. It has become an increasingly popular tool for motivating individuals to adopt healthier lifestyles. Lifestyle gamification is essentially treating your life as if it were a game. This paper provides an overview on gamification lifestyle with examples.